Answer:
>
Step-by-step explanation:
For this case we have that by definition, the Pythagorean theorem states that:

Where:
a, b: Are the legs
c: It is the hypotenuse
According to the figure we have to:

Substituting in the formula we have:

Answer:
Option D
2x-4y=-16
ax+4y=6 +
--------------------
2x+ax=-10; for x=-2,
2(-2)+a(-2)=-10
-2a=-10+4
a=-6/-2
a=3
Answer:
2(2y−7)(x+4)
Step-by-step explanation:
Factor 4xy−14x+16y−56
4xy−14x+16y−56
=2(2y−7)(x+4)
Answer:
I think it is b. Curve
Step-by-step explanation: